2020
DOI: 10.21203/rs.3.rs-49027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Has Fiscal Decentralization Influenced the Quality of Life in Sub-Saharan Africa? Empirical Evidence From Nigeria

Abstract: Sub-Sahara Africa countries has the highest proportion of people with the lowest access to basic amenities required to live well. Nigeria contributes significantly to the low quality of life in the region. Many governments particularly in Africa adopted government decentralization as a major policy reform to improve the distribution of public goods and services. The overall outcome of government decentralization is believed to be more dependent on the extent of fiscal decentralization. This study examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The availability of health resources (including integrated healthcare center/pos pelayanan terpadu (posyandu), health personnel) did not bring any effect on increasing the quality of health of the community [22] due to scarcity of health infrastructure in an area. In addition, the results of other studies also concluded that government budgets did not have any significant effect on psychological health and health in general [23]- [25], similar to a study in Indonesia which also showed no significant effect in the short term [26]. The findings of previous studies still show inconsistencies.…”
Section: Introductionsupporting
confidence: 51%
“…The availability of health resources (including integrated healthcare center/pos pelayanan terpadu (posyandu), health personnel) did not bring any effect on increasing the quality of health of the community [22] due to scarcity of health infrastructure in an area. In addition, the results of other studies also concluded that government budgets did not have any significant effect on psychological health and health in general [23]- [25], similar to a study in Indonesia which also showed no significant effect in the short term [26]. The findings of previous studies still show inconsistencies.…”
Section: Introductionsupporting
confidence: 51%